Religiusitas dan Karakter Sosial Warga Rw 015 Jakasampurna Sebagai Fenomena Kesalehan : doi 10.58569/jies.v1i2.585 - syairozi, Ishak (Pascasarjana Universitas Islam Jakarta, 2023)
Character is a practical display of every individual action and attitude in his life. Human actions and attitudes cannot be separated from the religious values adopted and moral values in their environment. Everyone has an obligation to live out the teachings of their religion, and this shows the relationship of each individual to his God (Hablun min Allah). Nevertheless, religious piety within the framework of religiosity should be apparent in the social shalehan for every religious believer in the interaction of his or her life. The phenomenon in RW 015 residents, it seems that religious social values and social social values are different (partial) things. The religiosity of the community has not been closely related to social life in the environment, or in return. There is still a lack of understanding of religious teachings that are universal. So, what is the relationship between religiosity and social character of the residents of RW 015 Jakasampurna? The study aims to uncover the phenomenon of piety of RW 015 residents in the social interaction of life in their environment. This research uses qualitative research methods, using the Symbolic Interaction approach, which is one of the phenomenological model approaches. Examine the traditions and various cultural phenomena of a social community, or understand the social and psychological phenomena of a social community in certain aspects in depth. The expected results found the phenomenon of community piety RW 015 Jakasampurna, and found a concept of cultivating spiritual and social piety in practical life in society.